2007
DOI: 10.1111/j.1467-8381.2008.00272.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of granulosa cell apoptosis by death ligand–receptor signaling

Abstract: Several hundred thousand primordial follicles are present in the mammalian ovary, however, only 1% develop to the preovulatory stage and finally ovulate. The remainder will be eliminated via a degenerative process called ‘atresia’. The endocrinological regulatory mechanisms involved in follicular development and atresia have largely been characterized but the precise temporal and molecular mechanisms involved in the regulation of these events remain unknown. Many recent studies suggest that apoptosis in ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 93 publications
(100 reference statements)
0
21
0
Order By: Relevance
“…54: [454][455][456][457][458][459] 2008) n mammalian ovaries, more than 99% of follicles disappear during follicular growth and development, and this appears to be primarily due to apoptosis of follicular granulosa cells, as the biochemical and morphological characteristics of apoptosis have been observed in the granulosa cells of atretic follicles [1][2][3]. Apoptotic stimuli and intracellular apoptosis-signal transduction pathways in granulosa cells have not yet been determined, and many researchers have attempted to confirm the primary trigger of apoptosis and how the intracellular apoptotic signal is transmitted in granulosa cells [4][5][6][7]. Many apoptosis-related factors are implicated in follicular atresia, including cell death ligands and receptors, intracellular pro-and anti-apoptotic molecules, cytokines and growth factors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…54: [454][455][456][457][458][459] 2008) n mammalian ovaries, more than 99% of follicles disappear during follicular growth and development, and this appears to be primarily due to apoptosis of follicular granulosa cells, as the biochemical and morphological characteristics of apoptosis have been observed in the granulosa cells of atretic follicles [1][2][3]. Apoptotic stimuli and intracellular apoptosis-signal transduction pathways in granulosa cells have not yet been determined, and many researchers have attempted to confirm the primary trigger of apoptosis and how the intracellular apoptotic signal is transmitted in granulosa cells [4][5][6][7]. Many apoptosis-related factors are implicated in follicular atresia, including cell death ligands and receptors, intracellular pro-and anti-apoptotic molecules, cytokines and growth factors.…”
mentioning
confidence: 99%
“…Apoptotic stimuli and intracellular apoptosis-signal transduction pathways in granulosa cells have not yet been determined, and many researchers have attempted to confirm the primary trigger of apoptosis and how the intracellular apoptotic signal is transmitted in granulosa cells [4][5][6][7]. Many apoptosis-related factors are implicated in follicular atresia, including cell death ligands and receptors, intracellular pro-and anti-apoptotic molecules, cytokines and growth factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent findings [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] have suggested that apoptosis in follicular granulosa cells plays a crucial role in the regulation of ovarian follicular atresia; however, the intracellular signal transduction pathway for apoptois in granulosa cells is still largely unknown [20,21]. Moreover, we have previously suggested that apoptosis and proliferation in granulosa cells are dominantly regulated by a cell death ligand and receptor system (TNF and TNFR superfamily members) [18][19][20][21]. In the granulosa cells of porcine ovarian follicles, TNFα acts as a cell proliferation factor but not as an apoptotic factor [13].…”
mentioning
confidence: 99%
“…The TNFα-mediated apoptotic signaling pathway (TNFR1-dependent apoptosis) has been suggested to be as follows [1][2][3][4][5][6][7][8] In mammalian ovaries, more than 99.9% of follicles undergo a degenerative process known as "atresia", and only a few follicles selectively ovulate during ovarian follicular development and growth [15][16][17][18][19][20][21]. Our recent findings [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] have suggested that apoptosis in follicular granulosa cells plays a crucial role in the regulation of ovarian follicular atresia; however, the intracellular signal transduction pathway for apoptois in granulosa cells is still largely unknown [20,21]. Moreover, we have previously suggested that apoptosis and proliferation in granulosa cells are dominantly regulated by a cell death ligand and receptor system (TNF and TNFR superfamily members) [18][19][20][21].…”
mentioning
confidence: 99%